Genetic and Non-Genetic Effects on Semen Characteristics of Bali Cattle (Bos javanicus) - Gunawan Sitanggang; Raden Iis Arifiantini; J Jakaria (Indonesian Center for Animal Research and Development (ICARD), 2020)
The objective of this study was to evaluate effect of genetic and non-genetic factors on semen characteristics including ejaculate volume, sperm concentration, total sperm number and sperm moetility of Bali cattle. Semen data were collected from the National Centre of Artificial Insemination at Singosari, Malang, East Java, Indonesia. A total of 3,847 ejaculates of 17 Bali bulls from 2014 to 2016 were collected and evaluated. Data were analyzed by restricted maximum likelihood (REML) method using mixed models which the bull was a random effect, while age of bull, season of collection, frequency of ejaculation and collection intervals were the fixed effects. Results showed that age significantly affected all semen characteristics (P<0.01). Season affected only on sperm motility (P<0.01). Effect of frequency of ejaculation and collection intervals was significant on all studied variables (P<0.01), except sperm motility. Repeatability of ejaculate volume, sperm concentration, total sperm number and sperm motility was 0.43; 0.35; 0.32 and 0.31, respectively. It is concluded that age, frequency of ejaculation and collection intervals were the most factors affected semen characteristics of Bali cattle. Repeatability estimations of semen characteristics were moderate to high.